Orientasi Pasar Dan Inovasi Sebagai Determinan Keunggulan Kompetitif Dalam Industri Fashion Berbasis E-Commerce - Ratih Indriyani; Michelle Felicia (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Business sustainability and growth depend on its competitive advantage, market orientation, and innovation. Competitive advantage is a superior value obtained through a company's strategy, enabling the company to outperform its competitors. Business competitive capabilityis influenced by market orientation and business innovation. This study aims to analyze the influence of market orientation on competitive advantage through innovation in fashion businesses utilizing e-commerce. The type of research used is quantitative explanatory, with a purposive sampling technique for data collection. This study uses 100 MSMEs business owners in e-commerce based fashion businesses. Data analysis was performed using Partial Least Squares (PLS) with the help of SmartPLS. The results show that market orientation has a significant effect on competitive advantage, market orientation also has a significant effect on innovation, and innovation significantly affects competitive advantage.